An Analysis of Factors Influencing Sales Prices of Condominium Hotels on Jeju Island, Korea - Sungbum Oh, Seonju Song, Jongchil Shin (International Journal of Advanced Science and Technology, 2020)
Background/Objectives: The purpose of this study is to introduce the concept of Korean condominium hotels, which are widely sold in the Korea, and to examine factors affecting the sales prices of condominium hotels on Jeju Island.